What?s been happening to concentration in Irish industry 1991-2001 - McCloughan, Patrick (Economic & Social Studies, 2005)
This paper estimates concentration in Irish manufacturing industry (1991-2001) by applying the McCloughan and Abounoori technique for calculating the concentration ratio given grouped data. The results suggest high aggregate concentration, which appears less a function of multi-plant operations than in the past, possibly reflecting industrial policy changes. Industrial concentration appears higher on average in Ireland than in other countries and there is a significant relationship between concentration and upper-tail size inequalities, suggesting that it is the top 1 or 2 firms that typically determine concentration. Concentration does not appear to vary with foreign ownership or export activity in Irish industry.
Keywords: Aggregrate concentration; Manufacturing; Industrial concentration; Ireland; Industry